Solar-assisted tri-generation system with LCPV‑CPC and small-scale gas turbine for year-round clean energy in hot-dry climates - Ben Hamida, Mohamed Bechir; Rasheed, Rassol Hamed; Singh, Narinderjit Singh Sawaran; Taghavi, Mohammad (Scientific reports, 2025)
This study develops, dynamically simulates, and optimizes an integrated tri‑generation system for year-round electricity, heating, and cooling supply under the hot-dry climatic conditions of Baghdad, Iraq. The proposed configuration couples a low‑concentration hybrid PV–compound parabolic concentrator (LCPV-CPC) with dual small‑scale gas turbines, high- and low-grade water-source heat pumps, and an ammonia-water absorption chiller, coordinated through a following-electric-load (FEL) strategy. The primary objectives are to maximize primary energy savings, annual cost reduction, CO 2 emissions mitigation, and exergy efficiency by exploiting multi‑grade thermal integration and dispatch optimization. A methodological novelty lies in applying a Reference Vector Guided Evolutionary Algorithm (RVEA) with entropy‑weighted VIKOR analysis to achieve balanced trade‑offs among energy, economic, environmental, and thermodynamic criteria. Dynamic co‑simulation through Aspen HYSYS-MATLAB, validated against high‑quality experimental data, ensures predictive reliability. Results confirm substantial performance gains compared with a separate production facility: primary energy savings up to ~ 33%, annual cost savings exceeding 10% at favorable solar conditions, and CO 2 emission reduction approaching 50%. Parametric analysis shows that increased solar irradiance significantly improves environmental and economic outcomes, with economic feasibility achieved beyond ~ 472 W/m 2 average radiation. Exergy efficiency remains stable or slightly declines at high irradiance due to intensified off‑design irreversibilities. Optimal inlet water temperatures to the LCPV-CPC further enhance renewable contribution without notable thermodynamic penalties. The findings demonstrate a technically and economically viable pathway for sustainable tri‑generation in climates with strong solar resources and high cooling demand, offering a transferable optimization framework for future hybrid renewable–fossil energy applications in urban buildings.